Studi Populasi dan Habitat Owa Jawa (Hylobates moloch Audebert 1797) di Kawasan Wana Wisata Kali Paingan Linggo Asri, Pekalongan, Jawa Tengah - Putra, M. Fadhil Randa; Baskoro, Karyadi; Hadi, Mochamad (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2018)
Javan Gibbon (Hylobates moloch) is an Indonesian endemic primate found on Java, in the province of West Java and Central Java. It is an Endangered species by IUCN and protected by Ministry of Environment and Forestry regulation No. P20/2018. Wana Wisata Kali Paingan was known as Javan gibbon habitat in Central Java, although not much research have been done. This study aimed to find out the population data and habitat of Javan Gibbon. This study was conducted in Wana Wisata Kali Paingan during April until May 2018 and Line Transect method was used in two tracks, Kali Wadas and Jurang Jero, with 1 kilometer and 5 repetition each. Result showed that 12 individuals in 4 groups was found with the density was 13,75 individuals /km2 and 4,39 groups/km2. Then at 6,7 km2 representative area the estimation was obtained 92 individuals and 29 groups. Javan gibbons were distributed from 630-780 MASL with the different sizes of groups. There were 25 species in 21 families trees and 4 species in 4 family poles was found. The dominant species was bamboo (Bambusa vulgaris) and terap tree (Artocarpus elasticus). Javan gibbonâ€™s favorite food trees were Terap tree, Ficus (Urostigma glaberrium) and (Ficus sinuata). There were several families of food trees for Javan gibbons including Moraceae, Euphobiaceae, Meliaceae, Lauraceae, and Fagaceae.. Â Â Keywords : Javan gibbon, Population, Habitat, Wana Wisata Kali Paingan